Planejamento ambiental e sustentabilidade: conexões de saberes na comunidade São João Batista, arquipélago de Bailique - AP - Ferreira, Robson da Costa (2023)
This dissertation aimed to understand the interrelationships of local and traditional knowledge for sustainable environmental planning in the São João Batista community, in the Bailique-AP archipelago. In the construction and organization of the methodological process, an attempt was made to privilege local knowledge as essential and necessary knowledge in the elaboration of an efficient environmental planning and for a participatory territorial management. The realization took place through the following steps: 1) bibliographic survey of pre-existing studies on the territory; 2) conducting ethical procedures; 3) direct observation in loco to identify forms of use and occupation; 4) application of semi-structured questionnaires to outline the socio-environmental profile of the community; and 5) Knowledge Cartography workshop. The dynamics of each stage of the work was thought out and discussed together with community organizations, respecting the principles established by the Bailique community protocol and approved in advance by local leaders. The socio-environmental diagnosis pointed out that the difficulty in accessing quality education directly interferes with the families' income, making it necessary to accumulate tasks interspersed with subsistence activities to guarantee the family's livelihood. In addition, the absence of the state in the provision of services and infrastructure and public policies appropriate to the local reality was identified. The main forms of use and occupation of the territory are linked to the local way of life, in which the environment dictates the rules, where the management of açaí is the main activity. The main environmental problems in the region are related to the ways in which natural landscapes are used and occupied, which has resulted in increased environmental degradation and compromised ecological sustainability. Therefore, environmental planning, as a subsidy for ecological-economic zoning, needs to be based on the knowledge of local populations, through an interdisciplinary dialogue that transcends the technical-scientific field, giving protagonism and valuing the socio-cultural and environmental diversity existing in the territory as strategies for sustainable territorial development as an indicator of effective public policies for the people who inhabit the territory of São João Batista.